2021
DOI: 10.3390/fractalfract5040221
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Stochastic Transport of Particles with Self-Reinforcement and Mittag–Leffler Distributed Rest Times

Abstract: We introduce a persistent random walk model for the stochastic transport of particles involving self-reinforcement and a rest state with Mittag–Leffler distributed residence times. The model involves a system of hyperbolic partial differential equations with a non-local switching term described by the Riemann–Liouville derivative. From Monte Carlo simulations, we found that this model generates superdiffusion at intermediate times but reverts to subdiffusion in the long time asymptotic limit. To confirm this r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…For instance, similar non-Markovian rest states with Mittag–Leffler distribution have been proposed recently for self-reinforced transport of particles. 94 In a geophysical context the non-Markovian MIM model has been recently used in ref. 87 for the description of the movement of a tracer which can switch between the mobile zone (the bulk water of a river) and immobile zone (dead-end pores, the hyporheic zone, or biofilms).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, similar non-Markovian rest states with Mittag–Leffler distribution have been proposed recently for self-reinforced transport of particles. 94 In a geophysical context the non-Markovian MIM model has been recently used in ref. 87 for the description of the movement of a tracer which can switch between the mobile zone (the bulk water of a river) and immobile zone (dead-end pores, the hyporheic zone, or biofilms).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one can take into account multiplicative noises that might lead to noise-induced transitions [25] for a nonlinear cutoff switch model [18]. It would be interesting to take into account the stochastic anomalous intracellular transport of viruses and nanoparticles along microtubules to the perinuclear region [26][27][28][29]. Certainly, the anomalous endosomal movements have implications on their fusion and fission inside cells and therefore Rab5 to Rab7 conversion.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was shown that strong memory and reinforcement can generate superdiffusion in a continuous-time and finite-velocity strong memory model [31], even in the presence of rests [32]. However, when including a trapping state, the superdiffusion caused by reinforcement was only transient [33].…”
Section: Introductionmentioning
confidence: 99%